A lysosome-targeting dual-functional fluorescent probe for imaging intracellular viscosity and beta-amyloid. Issue 18 (12th February 2019) - Tan, Hui-ya; Qiu, Yu-tai; Sun, Han; Yan, Jin-wu; Zhang, Lei
Abstract : A lysosome-targeting dual-functional fluorescent probe was rationally designed and developed for imaging intracellular lysosomal viscosity and beta-amyloid. Abstract : A lysosome-targeting dual-functional fluorescent probe was rationally designed and developed for imaging intracellular lysosomal viscosity and beta-amyloid. More importantly, the real-time tracking of the dynamic movement of lysosomes, as vesicle structures, has been achieved usingLyso-MC .